2012
DOI: 10.1007/128_2012_346
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing the Quadruplex: From Fluorescent Ligands to Light-Up Probes

Abstract: Detection of quadruplex structures by visual methods is a major challenge of the quadruplex nucleic acid research area. Consequently, considerable efforts are under way for the discovery of quadruplex specific agents endowed with fluorescence properties. In this review chapter we propose a comprehensive and critical overview of the diverse molecular design and strategies that have been described to identify quadruplex-selective fluorescent probes. Innovative compounds as well as classical DNA dyes are reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
77
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 122 publications
(79 citation statements)
references
References 202 publications
1
77
0
1
Order By: Relevance
“…Several commercial fluorescent organic dyes have been developed for that purpose but despite their sensitivity, protocols taking advantage of the specificity of transition metal or lanthanide chelates have also been suggested because they enable easy integrated multi-analyte detection [16,64]. Several approaches have been tested, including bioconjugation of lanthanide chelates to oligodeoxyribonucleotides [65] and energy transfer (FRET) from UCNPs [66].…”
Section: Biosensing and Bioanalysismentioning
confidence: 99%
“…Several commercial fluorescent organic dyes have been developed for that purpose but despite their sensitivity, protocols taking advantage of the specificity of transition metal or lanthanide chelates have also been suggested because they enable easy integrated multi-analyte detection [16,64]. Several approaches have been tested, including bioconjugation of lanthanide chelates to oligodeoxyribonucleotides [65] and energy transfer (FRET) from UCNPs [66].…”
Section: Biosensing and Bioanalysismentioning
confidence: 99%
“…Finally, we highlight recent examples of G-quadruplex small-molecule probes that have been used as G-quadruplex DNA imaging agents in living cells. Here, we focus mainly on examples that have been described in the last few years, as previous reviews on G-quadruplex probes describing earlier developments have been published by our group and others (Neo et al, 2012;Largy et al, 2013;Ren et al, 2015;Ruttkay-Nedecky et al, 2013;Vummidi et al, 2013). For ease of access, a summary of the photophysical properties of the G-quadruplex probes highlighted in this review can be found in Table 1.…”
Section: Introductionmentioning
confidence: 94%
“…Putative G-quadruplex-forming sequences are highly prevalent in human genes, especially in promoter regions of oncogenes and telomere ends, they are considered to play important roles in vivo in regulating the expression of many genes [8][9][10]. As a result, great efforts have been made to design and synthesize G-quadruplex ligands in the past decade [11,12]; most of these ligands contain an aromatic planar core that binds to G-quadruplex through π-π stacking interactions [13].…”
Section: Introductionmentioning
confidence: 99%